Challenges and Strategies in Supporting Students with Acquired Blindness (Interdisciplinary Studies Journal, 2024)
This article aims to better understand the perceptions of students with acquired blindness, regarding the rehabilitation process at the Visual Impairment Resource Room of the Social Inclusion Care Center – CAIS, in the Municipality of Diadema - SP. The study was conducted with 5 (five) students, all adults in different age groups, through a qualitative research approach, using semi-structured individual interviews as a data collection instrument. The purpose of the study was to plan, based on the analysis of the students' perceptions, improvements in the conduct of the teaching-learning process for rehabilitation, as well as in the experience at the Center, focusing on working with the students' self-esteem. The results indicate that the main aspect or goal of a person with acquired blindness in their rehabilitation process is social reintegration, with the acquisition of reading and writing, as well as orientation and mobility, being the main means or tools that the educator can use to contribute to this reintegration process. In addition to the rehabilitation methods or process itself, it was demonstrated by the applied research, and particularly by the observations made, that the psychological aspect is the primary issue or barrier to be overcome, requiring special attention from the educator.
Keywords: Visual Impairment; Acquired Blindness; Resource Room; Rehabilitation